PENGARUH CURRENT RATIO (CR) DAN DEBT TO EQUITY RATIO (DER) TERHADAP RETURN ON ASSET (ROA) PADA PT MAYORA INDAH TBK PERIODE 2009 – 2020 - Rita Satria (Sekolah Menengah Kejuruan (SMK) Pustek, 2022)
This study aims to determine whether there is a significant effect between Current Ratio (CR) and Debt to Equity Ratio (DER) on Return On Assets (ROA) at PT Mayora Indah Tbk for the 2009-2020 period, either partially or simultaneously. The method used in this study is a quantitative descriptive research method, using secondary data from the financial statements and annual report of PT Mayora Indah Tbk for the 2009-2020 period. The population of this study is the financial statements of PT Mayora Indah Tbk and the sample of this study is data that comes from the financial statements in the form of a balance sheet and income statement at PT Mayora Indah Tbk for the 2009-2020 period. The data analysis technique used in this research is descriptive statistical analysis test, classical assumption test (normality test, multicollinearity test, heteroscedasticity test, autocorrelation test), regression test (simple linear regression analysis, multiple linear regression analysis), correlation coefficient test, test coefficient of determination, hypothesis testing (partial test/T test and simultaneous test/F test). Based on the results of the research, the results of the t-test obtained t-count Current Ratio (CR) -0.004 < ttable 2.262 and the value of Sig 0.997 > 0.05, meaning that it partially has no effect and is not significant between the Current Ratio (CR) to Return On Assets (ROA). And tcount Debt to Equity Ratio (DER) of -2.463 > ttable 2.262 and Sig value of 0.036 <0.05, which means partially Debt to Equity Ratio (DER) has a negative and significant effect on Return On Assets (ROA). For the F test, it is obtained that Fcount is 4.224 > ttable is 4.10 and Sig value is 0.051 > 0.05, which means that simultaneously Current Ratio (CR) and Debt to Equity Ratio (DER) have a positive and insignificant effect on Return On Assets (ROA).